Pamana A short film narrative on Ifugao myths and stories to promote cultural consciousness among the urban youth - Lopez, Roselle G. (2013)
This short narrative film entitled Pamana meaning 'heritage' whose aim is to promote cultural consciousness among the urban adolescent youth. The Ifugao culture and oral heritages are in danger of fading because of the changes in technology, prevalence of foreign influences, and the lack of written materials of these heritages. This aims to retell stories that have been passed down from generations by the people who build our world wonder, the rice terraces. The Ifugao are a powerful representation of the Filipinos. Knowing their stories and the stories of other ancient Philippine groups will strengthen the Filipino people's sense of cultural identity as well as their self-esteem as a nation and continue to preserve their oral traditions.